2023
DOI: 10.1037/sah0000371
|View full text |Cite
|
Sign up to set email alerts
|

Stressful experiences and postpartum depressive symptoms among Asian and Pacific Islander women in the U.S.: The significance of racial discrimination.

Abstract: Asian and Pacific Islander (API) women are at higher risk of postpartum depression (PPD) compared with White, Black, and Hispanic women. However, research has rarely focused on investigating risk factors for PPD among API women in the U.S., nor has much research focused on the effects of racial discrimination on PPD. This study is one of the first to examine the association between multiple types of stressors and postpartum depressive symptoms (PPDS) among API women in the U.S., with a focus on the social stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…In our correlational criterion validity analysis, we found correlations between GRMS and postpartum anxiety and depression. These findings align with both findings from Lewis & Neville’s finding that GRMS is related to psychological distress, and previous research highlights associations between Global Majority pregnant and birthing people’s experiences of racism during birth and postpartum depression [ 44 , 45 , 52 ]. Likewise, the subgroup analyses demonstrated that postpartum depression was associated with GRMS among Asian, Black, and Hispanic participants, and anxiety was associated with GRMS among Black and Hispanic participants, further supporting the validity of the GRMS in Global Majority populations.…”
Section: Discussionsupporting
confidence: 90%
“…In our correlational criterion validity analysis, we found correlations between GRMS and postpartum anxiety and depression. These findings align with both findings from Lewis & Neville’s finding that GRMS is related to psychological distress, and previous research highlights associations between Global Majority pregnant and birthing people’s experiences of racism during birth and postpartum depression [ 44 , 45 , 52 ]. Likewise, the subgroup analyses demonstrated that postpartum depression was associated with GRMS among Asian, Black, and Hispanic participants, and anxiety was associated with GRMS among Black and Hispanic participants, further supporting the validity of the GRMS in Global Majority populations.…”
Section: Discussionsupporting
confidence: 90%